Antiproliferative, DNA binding, and cleavage properties of dinuclear Co(III) complexes containing the bioactive quinizarin ligand - Crlikova, Hana; Kostrhunova, Hana; Pracharova, Jitka; Kozsup, Máté; Nagy, Sándor; Buglyó, Péter; Brabec, Viktor; Kasparkova, Jana (Journal of biological inorganic chemistry, 2020)
The adverse side effects and acquired resistance associated with the clinical application of traditional platinum-based anticancer drugs have forced investigation of alternative transition metal-based compounds and their cytostatic properties. Over the last years, the anticancer potential of cobalt complexes has been extensively studied, and in-depth analyses of their mode of action have been conducted. In this work, we present antiproliferative activity against human cancer cells of the dinuclear Co(III) complexes bearing the quinizarin ligand and tris(2-aminoethyl)amine (tren, compound 1) or tris(2-pyridylmethyl)amine (tpa, compound 2) co-ligands. To contribute the understanding mechanisms of biological action of these compounds, their association with DNA in the cells, DNA binding in cell-free media, and DNA cleavage capability were investigated in detail. The results demonstrate that both complexes interact with DNA in tumor cells. However, their mechanism of antiproliferative action is different, and this difference is mirrored by distinct antiproliferative activity. The antiproliferative effect of 1 is connected with its ability to intercalate into DNA and subsequently to inhibit activities of DNA processing enzymes. In contrast, the total antiproliferative efficiency of 2, thanks to its redox properties, appears to be connected with its ability to form radicals and, consequently, with the ability of 2 to cleave DNA. Hence, the findings presented in this study may significantly contribute to understanding the antitumor potential of cobalt complexes. Dinuclear Co(III) complexes containing the bioactive quinizarin ligand exhibit antiproliferative activity based on distinct mechanism.
Keywords: komplexní sloučeniny; lidé; Coordination Complexes; Cell Proliferation; Cobalt; Antineoplastic Agents; Molecular Conformation; screeningové testy protinádorových léčiv; Tumor Cells, Cultured; Quinizarin; nádorové buňky kultivované; protinádorové látky; DNA; štěpení DNA; Humans; Binding Sites; kobalt; proliferace buněk; Radicals; DNA Cleavage; Anthraquinones; anthrachinony; ligandy; Drug Screening Assays, Antitumor; Ligands; vazebná místa; molekulární konformace; Antiproliferative activity